ANALYSIS OF FACTORS INFLUENCING THE INCREASING INTEREST OF GENERATION Z IN SURABAYA RAYA IN INVESTING IN GOLD AND STOCKS - Ratih Nindha Maylany Putri; Debora (CV. Fahr Publishing, 2024)
This study analyzes the factors that affect the interest of Generation Z in Greater Surabaya to invest in gold and stock instruments. Using a quantitative approach, data were collected from 70 respondents through a questionnaire and analyzed using multiple linear regression. The results showed that only investment trends had a significant effect on investment interest, while financial stability, investment knowledge, and profit expectations did not have a significant influence. These findings emphasize the importance of social media and technology trends in encouraging Generation Z to invest.